Four-loop critical exponents for the Gross-Neveu-Yukawa models - Zerf, Nikolai; Mihaila, Luminita; Scherer, Michael (Physical review, 2017)
We study the chiral Ising, the chiral XY, and the chiral Heisenberg models at four-loop order with the perturbative renormalization group in 4−ε dimensions and compute critical exponents for the Gross-Neveu-Yukawa fixed points to order O(ε4). Further, we provide Padé estimates for the correlation length exponent, the boson and fermion anomalous dimension, as well as the leading correction to scaling exponent in 2+1 dimensions. We also confirm the emergence of supersymmetric field theories at four loops for the chiral Ising and the chiral XY models with N=1/4 and N=1/2 fermions, respectively. Furthermore, applications of our results relevant to various quantum transitions in the context of Dirac and Weyl semimetals are discussed, including interaction-induced transitions in graphene and surface states of topological insulators.
Gesehen am 28.11.2017